Ablation of islet endocrine cells by targeted expression of hormone-promoter-driven toxigenes. - Herrera, P L (1994)
Ontogenic relationships between the different types of endocrine cells in the islets of Langerhans were explored by generating transgenic mouse embryos in which cells transcribing the glucagon, insulin, or pancreatic polypeptide genes were destroyed through the promoter-targeted expression of the diphtheria toxin A chain. Embryos lacking glucagon- or insulin-containing cells did not exhibit alterations in the development of the nontargeted islet cell types, whereas embryos lacking pancreatic polypeptide gene-expressing cells also lacked pancreatic insulin- and somatostatin-containing cells. These results show that neither glucagon nor insulin gene-expressing cells are essential for the differentiation of the other islet endocrine-cell types. These results also suggest that pancreatic polypeptide gene-expressing cells are indispensable for the differentiation of islet beta and delta cells because the former produce a necessary paracrine or endocrine factor and/or operate through a cell-lineage relationship.